Determinants of financial performance of electric power distribution utilities in the Philippines - Valderrama, Helen S.
Private utilities and electric cooperatives differed significantly in cost behavior and financial performance during the period 2000-2004. The study confirmed that electric cooperatives were generally operating in less viable areas characterized by lower average consumption per customer, less customer density, and higher proportion of residential sales to total sales. These environmental variables reflected in the higher average distribution costs of electric cooperatives. Nonetheless, the cost reimbursement scheme in the setting of rates for the sector mostly negated the impact of environmental variables on the DUs' financial performance. The study found that the most important determinants of the financial performance of Philippine distribution utilities, whether cooperative or private, pertained to cost recovery and systems loss, which were largely controllable by, rather than exogenous to, the firm. The high levels of inefficiency with which Philippine DUs operate implied that improvement in the financial performance of the sector needed to address this aspect of their operations.